Implementación de un curso interactivo bajo la plataforma moodle para la virtualización de los servidores en linux centos 7 como medio didáctico para los estudiantes de la carrera de ingeniería en informática y sistemas computacionales de la Universidad Técnica de Cotopaxi, durante el año 2015 - Quinatoa Pila, Verónica Maribel (2016)
This research details the implementation of an interactive course on the Moodle platform for server virtualization in Linux Centos 7 as a teaching tool for students of Computer Engineering and Computer Systems career at Technical University of Cotopaxi. The interactive course is a tool that allows interaction distance among users thought a network in order to develop students’ knowledge in the teaching process and satisfy their concerns and doubts respectively. The main objective of this research is to implement an online interactive course which will provide a lot of help to students and teachers, since, they can access information from any distance through the internet. To develop the interactive course Moodle educational platform was used and it is a dynamic learning environment and modular object-oriented. The methodology used in the development of the interactive course is PACIE, since, this is an online methodology through a virtual campus and the use of different teaching resources, which provides solid and basic bases for the researching development. To access the interactive course students should be enrolled and have their username and password respectively….